Metallenes as functional materials in electrocatalysis. (7th May 2021) - Prabhu, P.; Lee, Jong-Min
Abstract : 2D metals, metallenes, feature exciting opportunities at the forefront of electrocatalysis. We bring to attention metallene preparation techniques and modification strategies for the derivation of highly functional metallenes in key electrocatalytic applications. Abstract : Metallenes, atomically thin layers composed primarily of under-coordinated metal atoms, have emerged as the newest members in the family of 2D nanomaterials. Furthermore, the remarkable physicochemical properties associated with metallenes coupled with the ease of applying chemical modifications result in exciting opportunities towards catalyst engineering for electrochemical conversions. Especially in recent years, interest around metallenes has grown, evidenced by the surge in available literature. As such, it is imperative to review the findings and present directions for the future. In this review, we highlight the techniques available for deriving metallenes and further discuss the modification strategies commonly employed in devising metallenes to better suit applications in electrocatalysis. We provide a rational understanding of how each strategy drives performance enhancements and present gaps in the knowledge, necessary for further advancements in the field.